IMPLEMENTATION TECHNOLOGY ACCEPTANCE MODEL (TAM) ON ACCEPTANCE OF THE ZOOM APPLICATION IN ONLINE LEARNING - Ahmad Faisal; Frisma Handayanna; Indah Purnamasari (Jurnal Riset Informatika, 2021)
Abstract The application of online learning in various educational institutions in the Covid-19 Pandemic has had an impact on behavioral attitudes where many educators and students have also complained about the limited technology facilities, operations, and internet networks in some areas or quotas to access online learning. Followed by the popularity of the Zoom application in supporting education, the authors researched the application of the Technology Acceptance Model (TAM) to the acceptance of the Zoom application in online learning to determine the effect of using applications in online learning with 4 variables accompanied by multiple linear regression hypothesis testing, F-test and T-test. using SPSS. The test results in Perceived Usefulness, Perceived Ease of Use, and Behavioral Intention to Use affect Actual System Usage with significant and positive results of 20.21. Behavioral Intention to Use is more dominant than other variables with a value of 5.31, while the lowest is Perceived Ease of Use with a value of (-0.50).